Pyrrolizidine Alkaloid Contamination in Medicinal Plants: Regulatory Requirements and Their Impact on Production and Quality Control of Herbal Medicinal Products - Steinhoff, Barbara (Planta Medica, 2021)
Against the background of potential contamination of medicinal plant materials with pyrrolizidine alkaloids caused by weeds, suppliers of herbal drugs and manufacturers of herbal medicinal products have taken action by establishing a Code of Practice by monitoring potential contamination and by collection of data. In August 2020, the Herbal Medicinal Products Committee, in its new draft public statement, proposed a daily intake of 1.0 µg of pyrrolizidine alkaloids per day for adults in general, also including contaminations of herbal medicinal products. Over the past years, the results of data collections showed a remarkable reduction of the pyrrolizidine alkaloid burden in herbal drugs and herbal extracts. Meanwhile, a stable situation has been achieved for herbal drugs, while further improvement can be observed for herbal extracts. The results indicate that the implemented measures have been efficient and contribute to a continuous and sustainable reduction of pyrrolizidine alkaloid contamination. A permanent limit of 1.0 µg of pyrrolizidine alkaloids per day is considered appropriate to guarantee sufficient availability of batches used for the production of herbal medicinal products. The new Ph.Eur. general chapter 2.8.26 describes, as an example, an analytical procedure suitable for the determination of target pyrrolizidine alkaloids.
Keywords: pyrrolizidine alkaloids; herbal medicinal products; contamination; limits; Code of Practice